Oxford first book of Space - Langley, Andrew (England : Oxford university press, 2003)
"Oxford First Book of Space" is a book that takes you on a fun trip to learn about space. It shows you cool pictures of things like planets, stars, and rockets. The book tells you easy-to-understand facts about what's out there. It's a great first look at the amazing world beyond Earth!
Oxford First Book of Space" is a simple and fun book for anyone curious about what's out in space. It uses easy words and lots of colorful pictures to show you planets, stars, the Moon, and even rockets. You'll learn basic and interesting things about these amazing parts of our universe. It's a great way to start exploring the wonders of space!
Keywords: Oxford first book of space